TOWARD A BETTER FEDERAL INCOME TAX. - Mann, Everett J. (The Accounting Review, 1953)
Abstract Between the end of World War II and the outbreak of the Korean police action, the subject of tax reform engaged considerable attention from the U.S. Congress. Since 1945, certain inequities in the law have been removed; a few loopholes have been closed while others have been enlarged. Meanwhile, the income tax monster has grown apace. Under the new administration, a serious study of tax revisions, already labelled as the "free enterprise" tax system, is being made. The changes that may eventuate under this system are presumed to be some mitigation of the double tax on dividends, shortening of the holding period for long term capital gains, easing of the tax impacts on new enterprises, a more liberal approach to allowable depredation and similar changes designed to encourage risk taking. The time for enactment of emergency tax legislation would be simultaneous with Congressional recognition that an emergency existed. A tax reduction might mean the continuance of budget deficits in times of burgeoning prosperity. With huge expenditures predictable for years in advance, the taxpaying public should be given assurances as to where it stands. Tax bills should be kept fair and equitable as the national need and income dictates.